Environmental impact assessment of double- and relay-cropping with winter camelina in the northern Great Plains, USA. (September 2017) - Berti, Marisol; Johnson, Burton; Ripplinger, David; Gesch, Russ; Aponte, Alfredo
Abstract: Recent findings indicate that double- or relay-cropping winter camelina ( Camelina sativa L. Crantz.) with, forage, or food crops can increase yield per area, improve energy balance, and provide several ecosystem services. Double-cropping can help balance food and energy production. The objective of this study was to determine the environmental impact of double- and relay-cropping systems as compared with monocultured maize ( Zea mays L.) and soybean [ Glycine max (L.) Merr.] in the Midwest, USA. Ten crop sequences composed of double- and relay-cropped forage sorghum [ Sorghum bicolor (L.) Moench.] and soybean with winter camelina were evaluated and compared with their monoculture counterparts. The environmental aspects evaluated included global warming potential (GWP), abiotic depletion, acidification, eutrophication, ecotoxicity, and human toxicity. Additionally, provisioning and regulating ecosystem services were estimated, including: primary aboveground productivity, soil erosion, and biodiversity in each crop sequence. The analysis was conducted from 'cradle-to-gate', including only the agricultural phase. Global warming potential estimated by three different methods indicated that winter camelina as a monocrop had a GWP of 579 to 922 kg CO2e ha − 1 . Maize in monoculture had higher GWP than all other double- and relay-cropping systems studied. The higher emissions of double- and relay-cropping systems and maize can be explained by higher N fertilizer application, which led to greater field N2 O emissions. Also, the additional sowing and harvesting of the double- or relay-crop increased CO2 emissions due to increased diesel use. Winter camelina as a monocrop had the lowest values in all impact categories, indicating camelina agricultural production phase has low environmental impact compared with maize and soybean in monoculture. Double- and relay- cropping systems increased primary productivity per unit area and biodiversity and reduced soil erosion potential. Increasing productivity with the additional environmental benefits of these systems may encourage more farmers to adopt sustainable agricultural practices. Highlights: Winter camelina agricultural production phase presents lower environmental impacts than maize and soybean in monoculture Double- and relay- cropping had greater impact in global warming potential (GWP) than soybean and forage sorghum monoculture Maize in monoculture had higher GWP than all other double- and relay- cropping systems studied. Double- and relay- cropping systems increased biodiversity and reduced potential soil erosion. The realized environmental benefits of these systems may encourage farmers to adopt sustainable agricultural practices.